26th Annual Conference of the International Group for Lean Construction 2018
DOI: 10.24928/2018/0511
|View full text |Cite
|
Sign up to set email alerts
|

Envision of an Integrated Information System for Projectdriven Production in Construction

Abstract: Construction frequently appears at the bottom of productivity charts with decreasing indexes of productivity over the years. Lack of innovation and delayed adoption, informal processes or insufficient rigor and consistency in process execution, insufficient knowledge transfer from project to project, weak project monitoring, little crossfunctional cooperation, little collaboration with suppliers, conservative company culture, and a shortage of young talent and people development are usual issues. Whereas work … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…This sample is listed in Table 6. Guidelines to develop a BIM model focused on construction planning and control [28] 10 Using technology to achieve lean objectives [56] 11 Development of an integrated BIM and lean maturity model [57] 12 CAN BIM furnish lean benefits-An Indian case study [58] 13 Envision of an integrated information system for project-driven production in construction [59] 14 Evaluation of a case study to design a BIM-based cycle planning concept [60] 15 An exploration of BIM and lean interaction in optimizing demolition projects [61] 16…”
Section: Final Sample Overviewmentioning
confidence: 99%
“…This sample is listed in Table 6. Guidelines to develop a BIM model focused on construction planning and control [28] 10 Using technology to achieve lean objectives [56] 11 Development of an integrated BIM and lean maturity model [57] 12 CAN BIM furnish lean benefits-An Indian case study [58] 13 Envision of an integrated information system for project-driven production in construction [59] 14 Evaluation of a case study to design a BIM-based cycle planning concept [60] 15 An exploration of BIM and lean interaction in optimizing demolition projects [61] 16…”
Section: Final Sample Overviewmentioning
confidence: 99%
“…Recent studies have investigated the integration of AR with Lean and BIM. For instance, Antunes and Poshdar (2018) developed a theoretical framework for an information integration system for construction and indicated that BIM and AR can support project planning. (Calderon-Hernandez and Brioso 2018).…”
Section: Introductionmentioning
confidence: 99%